INFLUENCE OF ATTITUDE, SUBJECTIVE NORM, PERCEIVED BEHAVIOUR CONTROL TO PERFORM INTENTION IN PREVENTION ACTION OF DIABETES - Shofwanto Adhi Isnanda; Ira Nurmala (Universitas Airlangga, 2022)
Introduction: This study aimed to identify influence of attitude, subjective norm, and perceived behavior control to intention on preventive behavior of type II diabetes in Theory of Planned Behaviour model. Methods: This study is an observational study with a cross-sectional and analytical design. The population in this study were all undergraduate students of Public Health FKM UA. The sample was determined by using simple random sampling technique, until a total sample of 234 respondents was obtained. Result: Research on type II preventive behavior showed that respondents who agreed to the positive impact of preventive behavior of type II diabetes and had confidence that they could implement preventive behavior of type II diabetes by 70.08% of the total respondents. Respondents who had subjective norms agree on preventive behavior of type II diabetes and havmd the confidence to be able to perform preventive behavior for type II diabetes by 70.09% of the total respondents. Respondents who had the confidence to be able to interpret themselves were able to perform preventive behavior of type II diabetes and had confidence in carrying out preventive behavior for type II diabetes by 47.44% of the total respondents. Conslusion: Based on the results of the study showed that the attitude variable (P < 0.905) did not significantly influence the intention variable. While the subjective norm (P > 0,001) and perceived variables control (P > 0,001) significantly influence intention. Keywords:Type II Diabetes Mellitus, Prevention, TPB